Monitoring of hepatitis B virus surface antigen escape mutations and concomitant nucleostide analog resistance mutations in patients with chronic hepatitis B - Deshkar, Smita T.; Patil, Niranjan B.; Lad, Ashish A.; Papal, Namrata S.; Sharan, Swati S. (International Journal of Research in Medical Sciences, 2022)
Background: In hepatitis B virus (HBV), reverse transcriptase (RT) region of the polymerase P gene and surface S gene (HBsAg) are largely overlapped. Mutations in surface S gene may cause escape variants. In the present study, we aimed to study the prevalence and pattern of the typical HBsAg escape mutations and concomitant nucleos(t)ide analogue resistance mutation patterns in patients with chronic hepatitis B (CHB) in Indian population. Methods: The present observational study was carried out from January 2021 to June 2022 with 156 known cases of CHB infection. Hepatitis B viral load quantitation was done followed by HBV genotyping and drug resistance detection by PCR and sequencing. Results: Out of 156 cases of CHB, HBsAg escape mutations were found in 50 (32.05%) patients. Genotype D was predominant (90%). Median viral load was 4.43×105 copies/ml. Total 128 HBsAg escape mutations of 46 different patterns were observed with overall prevalence of 29.49% (46/156) in CHB infected patients. The most common substitutions were sP127T (16.67%), sA128V (14.74%), sR122K (5.13%), sY134N (3.85%), sK141R (2.56%), sS143L (2.56%) and sT126INST (1.92%). Concomitant RT mutations were detected in 20 (40%) patients. Total 68 (43.59%) RT mutations of 18 different mutation characteristics were found conferring possible or confirmed resistance to nucleos(t)ide analogues. Conclusions: The emergence of drugs resistant mutants with alteration in ‘aa’ determinant of the S protein is of some concern. The development of novel nucleos(t)ide analogues with a high barrier to resistance is warranted. National surveillance networks should be set up.